Brain age gap reduction following exercise mirrors clinical improvements in schizophrenia spectrum disorders - Yilmaz, Deniz; Papiol, Sergi; Keeser, Daniel; Cole, James H.; Malchow, Berend; Walter, Henrik; Meyer-Lindenberg, Andreas; Hirjak, Dusan; Hasan, Alkomiet; Schmitt, Andrea; Falkai, Peter; Maurus, Isabel; et al. (NeuroImage: Clinical, 2025)
Schizophrenia spectrum disorders (SSD) are associated with accelerated brain aging, reflected in an increased brain age gap. This gap serves as a biomarker, indicating poorer brain health, cognitive deficits, and greater severity in specific symptom domains. Exercise holds promise as an adjunct therapy to mitigate these deficits by potentially promoting brain recovery. However, the extent of overall improvements in brain health following exercise, along with their predictors and relationships to symptom clusters, are yet to be determined. This study examined the brain age gap metric as a quantitative indicator of brain recovery in response to exercise. To achieve this, we aggregated data from two randomized controlled trials, analyzing baseline (n = 134) and 3- or 6-month post-exercise (n = 46) data from individuals with SSD. Our findings revealed that patients with a higher baseline body mass index (BMI) demonstrated greater brain recovery, as evidenced by a reduced brain age gap post-exercise. Furthermore, changes in the brain age gap were associated with improvements in negative symptoms and cognition, suggesting that reductions in brain-predicted age may reflect symptom relief, particularly in domains beyond positive symptoms. These results underscore the importance of BMI in brain health, support using the brain age gap as a surrogate marker for tracking clinically relevant brain recovery, and highlight the need for stratified interventions and combined lifestyle modifications to enhance outcomes in SSD.
Online verfügbar: 19. September 2025, Artikelversion: 8. Oktober 2025
Gesehen am 01.12.2025